Learning of McDonald’s Operation Management & Consumer Behavior Analysis: A Qualitative Study - Nawangwulan, Irma M; Anantadjaya, Samuel PD; Agus Rachmat, Timotius (Malikussaleh University, Aceh, Indonesia, 2025)
This paper will discuss the overall operation management and the typical characteristics or behaviours of McDonald's consumers. The aim is to demonstrate McDonald's ability to comprehend the diverse facets of consumer purchasing behaviour and effectively manage its operations to address all potential challenges. The research method in this paper uses a descriptive qualitative approach. McDonald's is a globally recognised company in the fast-food industry. The operational strategy of McDonald's is to cut costs, boost product quality, guarantee timely delivery to consumers, and innovate continuously to improve performance. Fast food giant McDonald's can keep expenses down because of careful management. McDonald's never compromises on the quality of its food or service to its consumers. Fast food giant McDonald's uses a just-in-time system to meet customer demands for quick service and high-quality food on the go. Marketing and advertising widely employ the AIDA model to delineate the stages of consumer buying decisions and elucidate how advertisements engage and involve consumers in purchasing. McDonald's advertising employs the AIDA model to draw in consumers and create captivating ads that consistently attract new customers. Examining McDonald's marketing pillars is fascinating, as they are a key indicator of global success. McDonald's has developed a formula of four key elements that effectively maintain a business, set clear objectives, and effectively communicate with its customers.